Clinical characteristics and differential diagnosis of coronoid process hyperplasia - YOSHITAKE, Hiroyuki; WAKE, So; YODA, Tetsuya (Journal of the Japanese Society for the Temporomandibular Joint, 2023)
Coronoid process hyperplasia leads to limitation of mouth-opening due to contact of the enlarged coronoid process of the mandible with posterior surface of the body of the zygomatic bone and inner surface of the zygomatic arch. Patients suffering from coronoid process hyperplasia are often misdiagnosed and treated as cases of temporomandibular joint disorder because trismus secondary to coronoid process hyperplasia is relatively rare. To diagnose coronoid process hyperplasia, it is important to gather complete clinical information such as current medical history and clinical presentation, and to perform appropriate imaging tests. Coronoid process hyperplasia is characterized by comorbidity of other diseases related to the temporomandibular joint and masticatory muscles.This paper summarizes the clinical characteristics of coronoid process hyperplasia and the differences of coronoid process hyperplasia from other diseases with similar symptoms such as temporomandibular joint disorder.